PENERAPAN MODEL PEMBELAJARAN PAI BERBASIS DIGITAL (MICRO TEACHING) MODEL TEAM GAMES TOURNAMENT (TGT) - Eliva Sukma Cipta; Ayu Lavenia, Bunga; Yanti Lestari; Windary Sri Patimah; Muhammad Sakir; Akbar Agung Gumelar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the Team Games Tournament (TGT) learning model based on digital media in Islamic Religious Education (PAI) learning through micro teaching activities. The background of this research is the need for innovative and interactive learning strategies in the digital era to increase student engagement and understanding, especially in learning the history of the Umayyad Dynasty. This study used a qualitative descriptive approach. Data were collected through observation, documentation, and reflective notes during the learning process. The digital media used in this study included YouTube as a learning resource, Canva as an educational game medium, and Wordwall as an interactive evaluation tool. The results showed that the implementation of the digital-based TGT model created a more interactive, enjoyable, and student-centered learning atmosphere. Students demonstrated higher motivation, active participation, and better understanding of the material through group collaboration and academic games. In addition, the use of digital media helped teachers present historical material more visually and attractively. Although there were several obstacles, such as limited time and technological readiness, overall, the implementation of digital-based learning was proven effective in supporting the learning process of Islamic Religious Education in the modern educational era.